1979
DOI: 10.1104/pp.64.5.805
|View full text |Cite
|
Sign up to set email alerts
|

Production and Action of Ethylene in Senescing Leaf Discs

Abstract: Supraoptimal concentrations of indoleacetic acid (IAA) stimulated ethylene production, which in turn appeared to oppose the senescence-retarding effect of IAA in tobacco leaf discs. Kinetin acted synergistically with IAA in stimulating ethylene production, but it inhibited senescence. Silver ion and CO2, which are believed to block ethylene binding to its receptor sites, delayed senescence in terms of chlorophyll loss and stimulated ethylene production. Both Ethylene plays a considerable role in regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…This assumption is supported by the data showing that AgC, an antagonist of ethylene, could stimulate ethylene production in IAAtreated leaf discs (Fig. 5), probably because this agent could overcome the autoinhibitory effect of ethylene (3). The existence of an autoinhibitory mechanism in the ethylene biosynthesis pathway in the sugar beet system also can be demonstrated by the effect of propylene, an analog of ethylene.…”
Section: Resultssupporting
confidence: 71%
“…This assumption is supported by the data showing that AgC, an antagonist of ethylene, could stimulate ethylene production in IAAtreated leaf discs (Fig. 5), probably because this agent could overcome the autoinhibitory effect of ethylene (3). The existence of an autoinhibitory mechanism in the ethylene biosynthesis pathway in the sugar beet system also can be demonstrated by the effect of propylene, an analog of ethylene.…”
Section: Resultssupporting
confidence: 71%
“…Combination treatment of CO2 with Ag+ resulted in a strong synergistic effect on both ethylene production and retention of Chl ( Fig. 8 and Table I (5). The conclusion that the climacteric-like rise of ethylene production in senescent leaf discs could not have triggered leaf senescence was derived from previous studies (4, 6, 7), which showed that this rise occurs considerably after the commencement of Chl loss.…”
Section: Resultsmentioning
confidence: 60%
“…Concentrations above 50 mg/l AgNO3 markedly increased ethylene production and rates of respiration and yellowing; it also severely damaged the leaf discs, blackening the cut surface (data not shown). Apparently, induction of ethylene synthesis caused by relatively low concentrations of AgNO3 and the decrease in respiration are evidence not of Ag+ toxicity but of the antiethylene property of Ag+ (5).…”
Section: Resultsmentioning
confidence: 99%
“…Increased production of ethylene in response to enhanced levels of CO2 has been demonstrated for detached leaves and leaf discs of cocklebur (15), intact sunflower plants (6,12), tobacco leaf discs (1,2,18), and detached senescing oat leaves (14). The effect is obtained when CO2 is supplied either directly as a gas or indirectly as bicarbonate, and no increase in ethylene production ' is obtained when CO2 is removed with a KOH trap (15,18).…”
mentioning
confidence: 87%